2022
DOI: 10.1590/0001-3765202220210230
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanocrystals and Annona crassiflora Polyphenols Used Alone or Mixed Impact Differently on Wound Repair

Abstract: Wounds treated with TiO 2 nanoparticles (TiO 2 -NPs) show an improvement in healing time. However, little is known about the parameters that can contribute to this result. On the other hand, the treatment of wounds with polyphenols is widely known. These compounds are found in the peel of Annona crassifl ora fruit and have antioxidant, analgesic and anti-infl ammatory properties. In this study, we evaluated the healing effect of TiO 2 nanocrystals (TiO 2 -NCs), polyphenolic fractions obtained from ethanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Only phenolic-rich fractions (ethyl acetate (0.1 and 0.3 µg/mL) and n -butanol (1 µg/mL) fractions) reduced LPS-stimulated IL-6 and NO production. Topical treatment of wounds induced on the back of mice for 7–21 days with an ointment containing 4% of a phenolic-rich fraction from araticum peel was able to attenuate local inflammation by inhibiting MPO and NAG activities that reduce the activation of neutrophils and macrophages in cutaneous wounds [ 58 , 59 , 60 ]. Mice pre-treated orally with a phenolic-rich fraction (ethyl acetate fraction) from araticum peel (30 mg/kg bw) showed a reduced formation of CFA-induced paw edema in the acute phase due to the decrease in MPO activity and leukocyte infiltration in the paw tissue [ 56 ].…”
Section: Biological Activities Reported In Araticum Fruit Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only phenolic-rich fractions (ethyl acetate (0.1 and 0.3 µg/mL) and n -butanol (1 µg/mL) fractions) reduced LPS-stimulated IL-6 and NO production. Topical treatment of wounds induced on the back of mice for 7–21 days with an ointment containing 4% of a phenolic-rich fraction from araticum peel was able to attenuate local inflammation by inhibiting MPO and NAG activities that reduce the activation of neutrophils and macrophages in cutaneous wounds [ 58 , 59 , 60 ]. Mice pre-treated orally with a phenolic-rich fraction (ethyl acetate fraction) from araticum peel (30 mg/kg bw) showed a reduced formation of CFA-induced paw edema in the acute phase due to the decrease in MPO activity and leukocyte infiltration in the paw tissue [ 56 ].…”
Section: Biological Activities Reported In Araticum Fruit Partsmentioning
confidence: 99%
“…Prado et al [ 23 ] verified that a phenolic-rich extract from araticum seeds promoted keratinocyte (HaCaT) migration, leading to 73% of slot closure at 3.6 µg/mL. Animal trials conducted by de Moura et al [ 58 , 59 , 60 ] showed that topical application of an ointment, containing 4% of a phenolic-rich fraction from araticum peel, on wounds induced on the back of mice, for 7–21 days, accelerated the cutaneous wound closure by reducing local inflammation (decreased neutrophil and macrophage activation, as well as MPO and NAG activities) and oxidative damage (decreased lipid peroxidation while increased CAT activity), stimulating the profibrogenic process (increased number of mast cells and deposition of types I and III collagen fibers in wounds), promoting keratinocyte and fibroblast proliferation and migration (increased MMP-2 and MMP-9 activities), and improving dermis and epidermis organization during healing. This wound healing effect can be attributed to the ability of phenolic compounds present in these extracts/fractions (see Table 1 ) in modulating different biochemical pathways involved in the tissue repair process [ 6 ].…”
Section: Biological Activities Reported In Araticum Fruit Partsmentioning
confidence: 99%
“…Soft silicone and alginate were used as hydrophobic and hydrophilic dressing materials, respectively, and TiO 2 was deposited on them, employing the atomic layer deposition technique. Flexible dressings were maintained without sacrificing durability thanks to a nanoscale TiO 2 covering [ 159 ].…”
Section: Nanostructured Carriersmentioning
confidence: 99%
“…Major questions regarding the safety of ZnO NPs in sunscreens were related to their toxic potential in human umbilical vein endothelial cells (HUVECs), epidermal cells (A431), viable human keratinocytes, and fibroblasts, and it was demonstrated that ZnO NPs can induce cytotoxicity [11], oxidative stress [14] and DNA damage to skin [15]. Although TiO 2 NPs have been reported to be less toxic than other metal oxide NPs [16,17], and several reports have even shown their biosafety in skin applications [18][19][20][21], there have been several reports revealing their toxic damage to cell viability, oxidative stress, and cellular inflammation [22,23]. However, under the common situation of NPs co-applications, these single exposure reports from nanobiotechnological and nanotoxicological studies have been considered unrepresentative for actual consumer use.…”
Section: Introductionmentioning
confidence: 99%